2014
DOI: 10.1163/15692108-12341318
|View full text |Cite
|
Sign up to set email alerts
|

Food Security in South Asian Countries: 1972 to 2013

Abstract: The paper empirically examines the effects of trade liberalization reforms on food security in South Asia countries (sacs) using econometric analysis in a panel framework for the period from 1972 to 2013. The estimated results indicate that trade liberalization has a significant positive effect on food production and food security in the region. The results also endorse the role of agriculture factors in improving food production and food security in sacs. The findings indicate that food security is mainly a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 31 publications
0
1
0
1
Order By: Relevance
“…This is because women are regarded as pillars of the household; they are involved in agricultural production, care, and preparing and planning meals for their families [29,37,38]. These findings contradict the findings obtained in the study conducted in Niger, Brazil, which showed that male-headed households were more food secure than female-headed households [39,40] The household size (household members) influences the household structure, function, food demand, availability, and consumption. This study revealed that the household size positively influenced the consumption of fruits and vegetables but was insignificant.…”
Section: Discussionmentioning
confidence: 84%
“…This is because women are regarded as pillars of the household; they are involved in agricultural production, care, and preparing and planning meals for their families [29,37,38]. These findings contradict the findings obtained in the study conducted in Niger, Brazil, which showed that male-headed households were more food secure than female-headed households [39,40] The household size (household members) influences the household structure, function, food demand, availability, and consumption. This study revealed that the household size positively influenced the consumption of fruits and vegetables but was insignificant.…”
Section: Discussionmentioning
confidence: 84%
“…Based on more recent data, three studies have found that trade openness and tariff reduction are associated with increased calorie availability per capita [66], improved aggregate indicators of dietary diversity and quality [64], and decreased odds of being underweight for both rural and urban men and women [67]. The latter study, however, is based on cross-sectional household-level data, so further research would be needed in order to determine whether this association might be causal.…”
Section: Resultsmentioning
confidence: 99%
“…Jego znaczenie istotnie ewoluowa o i poszerzy o swój zakres, zarówno poj ciowy, jaki i przestrzenny. W ród prac po wi conych temu zagadnieniu odnale mo na liczne opracowania dotycz ce sytuacji ywno ciowej w uj ciu globalnym (Bne Saad, 2013;Schmitz i in, 2015;Maggio i in, 2015), w krajach Trzeciego wiata (FAO, 2015;Nkunzimana i in., 2016), krajach rozwijaj cych si (Anderson, Strut, 2012;Zakaria, Xi, 2014), ale równie krajach rozwini tych (Nyambayo, 2015;Borch, Kjaernes, 2016). Zagadnienie to jest tak e cz sto poruszane przez polskich autorów (Gulbicka, 2003;Ma ysz, 2009;Sapa, 2010;Miku a, 2012;Pawlak, 2012, Marz da-M ynarska, 2014Kraciuk, 2015;Paszkowski, 2015;Sadowski, 2015;Zegar, 2015;Kapusta, 2016).…”
unclassified